Protein Digestion-Derived Peptides and the Peripheral Regulation of Food Intake - Caron, Juliette; Domenger, Dorothée; Dhulster, Pascal; Ravallec, Rozenn; Cudennec, Benoit (Frontiers in Endocrinology, 2017)
The gut plays a central role in energy homeostasis. Food intake regulation strongly relies on the gut-brain axis and numerous studies have pointed out the significant role played by gut hormones released from enteroendocrine cells. It is well known that digestive products of dietary protein possess a high satiating effect compared to carbohydrates and fat. Nevertheless, the processes occurring in the gut during protein digestion involved in the short-term regulation of food intake are still not totally unraveled. This review provides a concise overview of the current data concerning the implication of food-derived peptides in the peripheral regulation of food intake with a focus on the gut hormones CCK and GLP-1 regulation and the relationship with some aspects of glucose homeostasis.